Culture Traits, Strength, and Organizational Performance: Moving Beyond “Strong” Culture - Saffold, Guy S. (Academy of Management Review, 1988)
It is reasonable to expect that a phenomenon as pervasive as organizational culture affects organizational performance. “Strong” culture models, however, oversimplify the relationship. If scholars are to accurately analyze culture-performance links, they must combine more appropriate measures of culture's impact with careful attention to intrinsically cultural performance-related organizational processes.